Styryl lactones from roots and barks goniothalamus lanceolatus - Rasol, Nurulfazlina Edayah; Ahmad, Fasihuddin Badruddin; Mai, Chun Wai; Bihud, Nur Vicky; Abdullah, Fauziah Hanum; Awang, Khalijah; Ismail, Nor Hadiani (SAGE Publications, 2018)
A new styryl lactone, 5R,6R-5-hydroxy-6-styryltetrahydropyrane-2-one 2 was isolated from the roots of an endemic Goniothalamus lanceolatus Miq. of Sarawak, Malaysia. Furthermore, seven previously undescribed diastereomers, 5R,6R-5-hydroxygoniothalamin 3, 5R,6R-5-acetylgoniothalamin 4, 6S,7S,8S-goniodiol-7-monoacetate 5, 6S,7S,8S-goniodiol-8-monoacetate 6, goniofupyrone B 7, deoxygoniopypyrone B 8 and 1S,5S,7R,8S,3-endo,7-endo-(+)-8-epi-9-deoxygoniopypyrone acetate 9, along with six known styryl lactones (1, 10-15) were also isolated and characterized. 6S-goniothalamin 1 is reported for the first time from a Goniothalamus species. 1, 11 and 12 showed cytotoxic activity against human colon and lung cancer cell lines with IC 50 values ranging from 2.38-7.59 µM.